Mad Cooperativism: Work, Community, and Labor Inclusion in Mental Health - Cea-Quintana, J (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2021)
This article addresses the meanings of work management and labor relations in the "Locooperativa" work community, a solidarity entrepreneurship that brings together people labeled with psychiatric diagnoses and people who have not had this experience through horizontal relationships, with the objective of generating economic income, guaranteeing the right to work and promoting labor inclusion in mental health. From a qualitative methodological approach and case study, the organizational characteristics and particularities of this self-managed work initiative are analyzed. In accordance with this experience, the contributions of "Mad Cooperativism" as a model of work management and the constitution of new labor relations for diversity and inclusion in contemporary Chile are described.